Lead exposure-induced defense responses result in low lead translocation from the roots to aerial tissues of two contrasting poplar species. (15th February 2021) - Shi, Wenguang; Zhou, Jing; Li, Jing; Ma, Chaofeng; Zhang, Yuhong; Deng, Shurong; Yu, Wenjian; Luo, Zhi-Bin
Abstract: To explore whether lead (Pb)-induced defense responses are responsible for the low root-to-shoot Pb translocation, we exposed saplings of the two contrasting poplar species, Populus  ×  canescens with relatively high root-to-shoot Pb translocation and P. nigra with low Pb translocation, to 0 or 8 mM PbCl2 . Pb translocation from the roots to aboveground tissues was lower by 57% in P. nigra than that in P.  ×  canescens . Lower Pb concentrations in the roots and aerial tissues, greater root biomass, and lower ROS overproduction in the roots were found in P. nigra than those in P.  ×  canescens treated with Pb. P. nigra roots had higher proportions of cell walls (CWs)-bound Pb and water insoluble Pb compounds, and higher transcript levels of some pivotal genes related to Pb vacuolar sequestration, such as phytochelatin synthetase 1.1 ( PCS1.1 ), ATP-binding cassette transporter C1.1 ( ABCC1.1 ) and ABCC3.1 than P.  ×  canescens roots. Pb exposure induced defense responses including increases in the contents of pectin and hemicellulose, and elevated oxalic acid accumulation, and the transcriptional upregulation of PCS1.1, ABCC1.1 and ABCC3.1 in the roots of P. nigra and P.  ×  canescens . These results suggest that the stronger defense barriers in P. nigra roots are probably associated with the lower Pb translocation from the roots to aerial tissues, and that Pb exposure-induced defense responses can enhance the barriers against Pb translocation in poplar roots. Graphical abstract: Image 1 Highlights: The root-to-shoot Pb translocation was lower in P. nigra than that in P.  ×  canescens . The stronger defense barriers were found in the roots of P. nigra . Pb-induced defense included cell wall remodeling and overexpression of key genes. Pb-induced responses enhanced the defense barriers against Pb translocation in roots. Abstract : The stronger defense barriers in P. nigra roots are associated with the lower Pb translocation from the roots to aerial tissues, and that Pb-induced defense responses can enhance the barriers against Pb translocation in poplar roots.